Classrooms Acoustic Evaluation to Enhance Quality of Teaching and Learning in Higher Education Institutions - L. Lindawati; M. Mahyuddin; Mery Silviana; Amilia Hasbullah (Jurnal Inotera, 2024)
The acoustical condition in the classroom frequently affects the quality of teaching and learning activities in higher education Institutions. Lecture activities require a favorable environment that is free of noise. The study aims to assess the acoustical condition of the C101 classroom, Engineering Faculty, Abulyatama University. Data collection was conducted by measuring Background Noise Levels and student perception of noise using a set of questionnaires. The result revealed that the average background noise level (BNL) measured in the classroom is 56,9 decibels. It shows that the BNL measured is greater than the noise permitted by the Indonesian government for the education area. The primary cause of this noise is the students activity inside the classroom during learning activities. In general, respondents are likely able to deal with noise existence within the classroom.